Debate: Money, Money, Money - Ellinger, Nina Ilona; Sharma, Seeta (Anti-Trafficking Review, 2014)
The question: ‘What would be the best way to use ten million dollars?’ leads to many other questions when related to anti-trafficking work. What should the money be spent on? Who should be appointed to spend the money? And, perhaps most importantly, who should be the beneficiaries? In other words, are the ten million dollars to prevent trafficking of people meant for activities to stop smuggling of people, to stop unwanted migrants, or to protect and uphold people’s rights when they move across borders and need to be protected from trafficking? Would the money be best spent on anti-trafficking work, or would it be better spent on strengthening the rights of all migrants to minimise the risk of trafficking?